KIPSAS goes back to basics - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
27 July 2010. A Basic Oral Communication Course was conducted for a day in Kolej Islam Pahang Sultan Ahmad Shah (KIPSAS) for 12 non academic staff. The objective of this course was to assist participants improve in their speaking in English.